The Relationship Between Leadership and Innovation in Educational Settings (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper investigates the relationship between leadership styles and the fostering of innovation in educational settings. It will explore how leadership can promote creative thinking, risk-taking, and experimentation among educators and students. The research will analyze different leadership approaches and their effectiveness in creating an environment conducive to educational innovation. The paper will discuss the importance of leadership in preparing students for the demands of a rapidly changing world.